Robust feedback control of continuously operated convective dryers for particulate materials - Seidel, C.; Neugebauer, C.; Durr, R.; Bück, Andreas (IDS'2018: 21ST INTERNATIONAL DRYING SYMPOSIUM, 2018)
Convective drying is a common process for the treatment of particulate solids also operated in continuous mode. Continuous operation is characterised by operation in steady-state with constant product throughput and constant product quality. Due to external influences, i. e. seasonal or local variations in the properties of the initial wet material, deviations in the product quality can result, for example over- or under-drying, or on-set of unwanted reaction. In this contribution a new feedback control concept is developed that is robust with respect to variations and uncertainties in the drying kinetics of the material and can reject and attenuate process disturbance
CRIS-Team WoS Importer:2019-08-16
Keywords: Process control; drying kinetics; robustness; fluidized bed; yeast